Leveraging Proteomics to Understand Plant–Microbe Interactions - Jayaraman, Dhileepkumar; Forshey, Kari L.; Grimsrud, Paul A.; Ané, Jean-Michel (Frontiers in Plant Science, 2012)
Understanding the interactions of plants with beneficial and pathogenic microbes is a promising avenue to improve crop productivity and agriculture sustainability. Proteomic techniques provide a unique angle to describe these intricate interactions and test hypotheses. The various approaches for proteome analysis generally include protein/peptide separation and identification, but can also provide quantification and the characterization of post-translational modifications. In this review, we discuss how these techniques have been applied to the study to plant-microbe interactions. We also present some areas where this field of study would benefit from the utilization of newly developed methods that overcome previous limitations. Finally, we reinforce the need for expanding, integrating, and curating protein databases, as well as the benefits of combining protein-level datasets with genetics and other high-throughput large-scale approaches for a systems-level understanding of plant-microbe interactions.